Measuring Employee Readiness for Knowledge Management Implementation in the Audit Board of the Republic of Indonesia - Risfayanti, Risfayanti; Muluk, M. R. Khairul; Putra, Fadillah (Badan Pemeriksa Keuangan Republik Indonesia, 2023)
The Audit Board of the Republic of Indonesia is one of the largest public institutions with frequent job rotations and high employee turnover. The current COVID-19 pandemic, which has forced employees to adopt work from home whether they are ready or not, has compelled the organization to implement knowledge management successfully urgently. Employee readiness is one of the critical factors in the implementation of knowledge management. If the employee is not ready, it will lead to the organization’s failure. This study aims to measure the level of employee readiness in BPK to implement knowledge management by using the intention to be involved in the SECI (Socialization, Externalization, Combination, and Internalization) process. The analysis was conducted by using SEM (Structural Equation Modelling). The result reveals that employees of BPK are ready to implement knowledge management. This is shown by the development of the SEM analysis and by the results of descriptive statistics with high values. The SEM analysis displays 14 out of 16 items considered the most representative dimensions in the SECI Process.